The Martian Surface 2008
DOI: 10.1017/cbo9780511536076.013
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral imaging from Mars Pathfinder

Abstract: The Imager for Mars Pathfinder (IMP) was a mast-mounted instrument on the Mars Pathfinder lander which landed on Mars' Ares Vallis floodplain on July 4, 1997. During the 83 sols of Mars Pathfinders landed operations, the IMP collected over 16,600 images. Multispectral images were collected using twelve narrowband filters at wavelengths between 400 and 1000 nm in the visible and near infrared (VNIR) range. The IMP provided VNIR spectra of the materials surrounding the lander including rocks, bright soils, dark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…2 ) and in the sedimentary rocks of Meridiani Planum ( e.g. , Bell et al 2004b ; Farrand et al 2007 , 2008 ; Weitz et al 2010 ) and has also been reported in Gale crater rocks (Ollila et al 2014 ; Lanza et al 2015 ).
Fig.
…”
Section: Mastcam-z Investigation Goalsmentioning
confidence: 86%
See 1 more Smart Citation
“…2 ) and in the sedimentary rocks of Meridiani Planum ( e.g. , Bell et al 2004b ; Farrand et al 2007 , 2008 ; Weitz et al 2010 ) and has also been reported in Gale crater rocks (Ollila et al 2014 ; Lanza et al 2015 ).
Fig.
…”
Section: Mastcam-z Investigation Goalsmentioning
confidence: 86%
“…Past Mars surface mission experience shows that even low spectral resolution RGB color and multispectral imaging with carefully-selected wavelengths can help investigators decide strategically and tactically along the traverse where to invest in resource-intensive arm-related or other rover activities, and to understand more clearly the context of mineralogic phases identified by other payload elements ( e.g. , Bell et al 2008 , 2020 ; Farrand et al 2008 ; Blake et al 2013 ; Vaniman et al 2014 ). In addition, fine-scale compositional imaging can help to constrain the mineralogy of small features.…”
Section: Mastcam-z Investigation Goalsmentioning
confidence: 99%
“…Consideration was given as to the number and types of materials used to characterize the sensors for VIS/NIR utility, particularly in the 600–800 nm (hereafter termed “ferric response”) portion of the spectrum. Color swatches of a known spectral value have been used in previous research to assist in measuring spectral output from sensors, including lander missions flown to Mars since the 1970s [ 15 , 17 , 22 ], multispectral [ 26 ] and hyperspectral applications [ 30 ]. The utility of three cameras for pushbroom sensor designs was trialed with minerals exhibiting phenomenology in the ferric response portion of the spectrum and that have been found in the inner solar system [ 15 , 16 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…This paper explores the application of hyperspectral technology to the appraisal of spectral responses of minerals of interest gathered during surface-based planetary robotic lander missions [ 15 , 16 , 17 ]. An attribute of lander-based spectral sensing is that the proximity of the sensor to the object of interest minimizes attenuation due to atmospheric effects as radiative or reflective energy reduces with increasing distance from the target.…”
Section: Introductionmentioning
confidence: 99%
“…Like Viking, Pathfinder acquired important new information on the nature of the martian surface via a combination of lander and rover imaging and other in situ elemental and meteorological measurements (e.g., Smith et al, 1997b;Golombek et al, 1999). Much more information on the compositional and mineralogic implications of IMP multispectral imaging is discussed in Chapter 12 (Farrand et al, 2007).…”
Section: Introductionmentioning
confidence: 99%